2022
DOI: 10.1371/journal.pone.0266433
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of cilia characteristics and Hedgehog signaling in five immortal cell lines

Abstract: Dysfunction of the primary cilium, a microtubule-based signaling organelle, leads to genetic conditions called ciliopathies. Hedgehog (Hh) signaling is mediated by the primary cilium in vertebrates and is therefore implicated in ciliopathies; however, it is not clear which immortal cell lines are the most appropriate for modeling pathway response in human disease; therefore, we systematically evaluated Hh in five commercially available, immortal mammalian cell lines: ARPE-19, HEK293T, hTERT RPE-1, NIH/3T3, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although favorable for GLI stabilization, these responses risk depleting cilia of cAMP, which can slow IFT and destabilize PC length homeostasis. Consistent with this scenario, we and others have observed that SHH stimulation of cultured murine fibroblasts or IMCD3 cells can trigger modest reductions in ciliary length that occasionally reach statistical significance (this study and Gomez et al [2022] ). However, SHH-stimulated IMCD3 PC shortening does not exceed ∼12% unless SHH-EP 4 crosstalk is blocked, whereupon length reductions are consistently significant and range from ∼25 to 40%.…”
Section: Discussionsupporting
confidence: 90%
“…Although favorable for GLI stabilization, these responses risk depleting cilia of cAMP, which can slow IFT and destabilize PC length homeostasis. Consistent with this scenario, we and others have observed that SHH stimulation of cultured murine fibroblasts or IMCD3 cells can trigger modest reductions in ciliary length that occasionally reach statistical significance (this study and Gomez et al [2022] ). However, SHH-stimulated IMCD3 PC shortening does not exceed ∼12% unless SHH-EP 4 crosstalk is blocked, whereupon length reductions are consistently significant and range from ∼25 to 40%.…”
Section: Discussionsupporting
confidence: 90%
“…Signal intensity profiles were obtained with the Plot Profile function of Fiji/ImageJ, also as described ( Cilleros-Rodriguez et al, 2022 ). For HEK293T cells, our protocol was the same, except for two modifications based on recent work: i) coverslips were coated with poly-L-lysine and gelatin; and ii) cells were not serum-starved, as this does not affect their ciliation ( Gomez et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…To associate the ciliation phenotype observed in patient cells with the TUBB G308S variant, the effect of the mutation must be studied in a context that is different from the patient's genetic background, and isogenic between control and mutant cells. Human hTERT-RPE1 cells are a common model to study primary cilia in vitro due to efficient ciliation and the functional properties of their cilium 40 . Therefore, we assessed ciliation in the TUBB G308S cell model compared to the isogenic TUBB WT cell line.…”
Section: The Tubb G308s Variant Causes a Primary Cilia Defectmentioning
confidence: 99%